Protein quality evaluation: FAO perspective - Xipsiti, Maria (Frontiers in Nutrition, 2024)
United Nations agencies have a unique role in achieving the Sustainable Development Goals (SDGs) and aligned global nutrition targets by 2030. According to the latest estimates the world is moving backward in its efforts to end hunger, food insecurity and malnutrition in the presence of a more challenging and uncertain context, including climate change, war conflicts and other challenges. Shifts to plant and novel foods such as insects have been suggested to have greater nutritional valuegood nutritional quality, as well as less environmental impact compared to "traditional" animal source foods. In the context of changing food systems, considering the nutritional quality of foods is essential and accurately assessing protein quality of foods is particularly important, given the large variability in amino acid composition and digestibility between dietary proteins. Indeed, protein quality estimates have the potential to inform policies and programs for actions to improve nutrition throughout the world and have been discussed during past and recent expert consultations. Recently, the Food and Agriculture Organization of the United Nations has been working with the International Atomic Energy Agency and international experts to review and update evidence and related methods on protein quality assessment and to develop a Protein Digestibility Database to aid dialogue on the evaluation of protein quality and protein sufficiency in different populations.